2013
DOI: 10.5704/moj.1307.009
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency-Induced Intradiscal Nucleoplasty Chronic Low Back Pain Secondary To Lumbar Disc Herniation

et al.

Abstract: We set out to assess the efficacy of radiofrequency-induced intradiscal nucleoplasty in reducing pain in symptomatic patients with MRI-defined lumbar disc herniation and their satisfaction with the procedure. We compared the patients’ pain intensity and severity of disability scores before and after undergoing the procedure in a retrospective questionnaire. These patients reported statistically significant reduction of pain intensity and disability level after the procedure. We conclude that radiofrequencyindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Radiofrequency nucleoplasty is a procedure employing coblation technology to coagulate and ablate the intervertebral disc with a low-temperature (52°C) plasma field results in minimal collateral damage to adjacent tissue. Radiofrequency nucleoplasty is considerably successful in relieving low back pain (4-7), decreasing morbidity, and shortening the recovery time (8). The current study reported a case with discitis following radiofrequency nucleoplasty.…”
Section: Introductionmentioning
confidence: 64%
“…Radiofrequency nucleoplasty is a procedure employing coblation technology to coagulate and ablate the intervertebral disc with a low-temperature (52°C) plasma field results in minimal collateral damage to adjacent tissue. Radiofrequency nucleoplasty is considerably successful in relieving low back pain (4-7), decreasing morbidity, and shortening the recovery time (8). The current study reported a case with discitis following radiofrequency nucleoplasty.…”
Section: Introductionmentioning
confidence: 64%
“…Radiofrequency nucleoplasty can be used as an alternative to surgical treatment for discogenic lower back pain [ 122 , 123 ]. This treatment can also be used for the treatment of radiating pain caused by cervical disc herniation [ 124 , 125 ].…”
Section: Spinal Injection Treatmentmentioning
confidence: 99%
“…This treatment can also be used for the treatment of radiating pain caused by cervical disc herniation [ 124 , 125 ]. While RF neurotomy involves neural ablation, RF nucleoplasty removes the disc matrix [ 122 , 123 , 124 , 125 ].…”
Section: Spinal Injection Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…coagulated nucleus pulposus, reduced intradiscal pressure and reduced pressure on the annulus fibrosus and nerve root. [4][5][6][7] Furthermore, RIN could relieve the symptoms of patients with lumbar disc herniation. 8 Kloth et al 9 reported that RIN could be preferred for treating radicular pain caused by disc herniation.…”
Section: Introductionmentioning
confidence: 99%